Variety of Meanings of Wisdom in the Qur'an - Rizki Maulana Putra; Gustiana Isya Marjani (Gunung Djati Conference Series, 2021)
This study aims to discuss the various meanings of wisdom in the Qur'an. This research method uses qualitative research through literature study with content analysis approach. The results of the discussion of this study include the definition of the word wisdom, the space for the existence of the word wisdom, the interpretation of the word wisdom in the Qur'an, and the meaning of the word wisdom in Surah Luqman verses 12-19. The conclusion of this study is that wisdom is a wise attitude that is based on two things, namely the ability to think and the ability to act. But all the meanings depend on the situation and condition of a verse of the Qur'an.